2005
DOI: 10.1364/ol.30.000543
|View full text |Cite
|
Sign up to set email alerts
|

Designing optical-fiber modulators by using magnetic fluids

Abstract: To reduce interface loss between optical fibers and devices in telecommunication systems, the development of an optical-fiber-based device that can be fused directly with fibers is important. A novel optical modulator consisting of a bare fiber core surrounded by magnetic fluids instead of by a SiO2 cladding layer is proposed. Applying a magnetic field raises the refractive index of the magnetic fluid. Thus we can control the occurrence of total reflection at the interface between the fiber core and the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 10 publications
0
58
0
2
Order By: Relevance
“…Based on these optical properties, many MF-based photonic devices can be made. Recently, some schemes for the applications of the MF to photonic devices have been proposed by some researchers and some sample photonic devices ͑for instance, MF light modulator, 21 MF optical switch, 22,23 MF coarse wavelength-division multiplexer, 24 MF Mach-Zehnder interferometer, 25 MF grating, 26 MF optical-fiber modulator, [27][28][29] etc.͒ have been demonstrated in the laboratories and their qualities have been experimented. An obstacle to the applications of the MF to practical use in the optical field is its relatively large extinction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these optical properties, many MF-based photonic devices can be made. Recently, some schemes for the applications of the MF to photonic devices have been proposed by some researchers and some sample photonic devices ͑for instance, MF light modulator, 21 MF optical switch, 22,23 MF coarse wavelength-division multiplexer, 24 MF Mach-Zehnder interferometer, 25 MF grating, 26 MF optical-fiber modulator, [27][28][29] etc.͒ have been demonstrated in the laboratories and their qualities have been experimented. An obstacle to the applications of the MF to practical use in the optical field is its relatively large extinction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…1 Interest to optical properties of ferrofluids has grown in the last decade 2 because of their applicability to ferrofluidic devices, 3 such as a magnetically controlled all-optical switch 4 and modulators, 5 and many research efforts have been devoted to this subject. Attractive possibilities are offered by a FF combination with microstructured optical fibers.…”
mentioning
confidence: 99%
“…Although a variety of remarkable effects, such as Hall effect (Ren et al 2005), shear-excited sound (Muller and Liu 2002), one-dimensional patterns (Wirtz and Fermigier 1994), solitons (Richter and Barashenkov 2005) convective instabilities (Luo et al 1999) and thermal lens effect (Pu et al 2005) have been observed in magnetic fluid, and fibers with ''magnetic'' cores have been theoretically investigated (Reyes and Rodriguez 1997), there are also some reports about magnetic fluids have been used as cladding (Chieh et al 2007;Horng et al 2005;Pu et al 2007), but no attempts were made to explore novel effects in magnetic fluid core fiber. More surprising results may be anticipated when such distinctive fluid is combined with optical fibers, as light can be strongly confined in the waveguide here.…”
Section: Introductionmentioning
confidence: 99%